Scaling gender-transformative socio technical innovation bundling for impact: Evidence of enhanced resilience, empowerment, food security, and incomes in Ethiopia - Ketema, Dessalegn; Lutomia, Cosmas Kweyu; Nchanji, Eileen Bogweh (2025)
This infographic presents evidence from collaborative gender-transformative interventions of CGIAR Gender Equality Initiative (HER+ - Harnessing Equality for Resilience in the Agri-food System), the SNV Netherlands Development Organisation (SNV), World Vegetable Center (Worldveg), and Lersha Platform of Green Agro Solution PLC in Welmera and Ejera woredas in Oromia region of Ethiopia. The evidence shows that gender-transformative socio-technical innovation bundling (GTSTIBS) and the resultant bundles were consistently associated with higher resilience, empowerment, improved food security and nutrition, and significantly greater household income. The benefits were observed across genders.